The Vietnam war : Vietnamese and American perspectives - Werner, Jayne S.; Huynh, Luu Doan (1993)
Abstract.
Keywords: Vietnamin sota : 1961-1975; sotahistoria Vietnam : 1961-1975; sotahistoria : USA : 1961-1975